Brine Evaporation Modeling in WAIV System Using Penman, Priestley-Taylor, and Harbeck Models - Herry Santoso; Dwiki Eka Putra; Giovanni Angelina; Yansen Hartanto; Judy Retti Bhawaningrum Witono; Kevin Cleary Wanta (Directorate for Research and Community Services, Institut Teknologi Bandung, 2022)
Indonesia is a maritime country with a vast ocean area. Indonesia has high potential to produce salt because it has a lot of saltwater resources. When sea salt is harvested, seawater evaporates from a concentration of 3.5°Be to 29°Be. Evaporation can be affected by several factors, such as air temperature, wind speed, water vapor pressure, humidity, radiation, geographical location, time interval, and season. Many modifications have been made to increase the evaporation rate in salt production. One of them is the WAIV (Wind-Aided Intensified eVaporation) method. WAIV evaporation systems utilize sunlight and wind to accelerate the evaporation rate. The modeling in this study was adjusted to the environmental conditions in the case study for which it was necessary to determine new parameter values for the existing models. The Penman, Priestley-Taylor, and Harbeck models were used. The Harbeck model has been studied in previous studies, which were used as a reference in the present study. This study first determined and then validated the parameter values obtained. A simulation of the evaporation rate was conducted in a different place, namely Kupang, East Nusa Tenggara, Indonesia using Meteorology, Climatology, and Geophysical Agency (Indonesian: Badan Meteorologi, Klimatologi, dan Geofisika / BMKG) data.